Os militantes no poder : lideranças negras nos espaços institucionais em Sergipe (2003-2015) - Silva, Aline Ferreira da (2016)
This study examines the process of emergence of black leaders in institutional governance spaces in Sergipe. Thus questioning about why these militants are in these areas and the conditions of access to them, the study not only shows the current scenario in which it operates racial politics in Sergipe, but also reflects on the dynamics of action, interaction and identity that black movements and government representatives trigger forward to these new joints. Although the investigative cut focus on the reality of the State of Sergipe, the study also aims to contribute to a broader reflection on the meaning of what is, for the state (governments) and civil society (black leaders), maintain a relationship of "partnership" and "consensus"; what are the real conditions of power faced by black leaders when they step into spheres of government; and what are the speeches and criteria triggered by the black movements and government representatives to defend the view that only blacks are the legitimate representatives of the black cause. Thus, the study has three main stages: first, an analysis of the narratives that advocate on the need for blacks represent blacks and thus step into the spheres of power; second, investigates the daily practices of "be in power" by checking the sites, forms and conditions for the participation of black militants in the institutional spheres; and third, it analyzes the process of fragmentation and disintegration of the promotional institutions of racial equality, causing disbelief of black activists in relation to the party and government spheres. At the end, we concluded that in the last ten years, black movements in Sergipe spent battling defenders, via governmental institution, to critics and disbelievers with it, seeking to remake its militancy based on a discourse of autonomy (party and institutional) and the specific direction for the race.